Effects of Different Dietary Starch Sources and Digestible Lysine Levels on Carcass Traits, Serum Metabolites, Liver Lipid and Breast Muscle Protein Metabolism in Broiler Chickens - Caiwei Luo; Yanhong Chen; Dafei Yin; Jianmin Yuan (Animals, 2023)
This study investigated the effects of digestible lysine (dLys) in different dietary starch sources on liver lipid metabolism and breast muscle protein metabolism in broiler chickens. The experimental design was a 3 × 3 two-factor completely randomized design. A total of 702 one-day-old male Arbor Acres Plus broilers were randomly divided into nine treatments of six replicate cages with thirteen birds each. The treatments consisted of three different starch sources (corn, cassava and waxy corn) with three different dLys levels (1.08%, 1.20% and 1.32%). The trial lasted from 1 to 21 days. Carcass traits, serum metabolites, breast muscle protein and liver lipid metabolism were evaluated. A significant interaction effect (p < 0.05) for dietary starch sources and dLys levels was noted in the percentage of abdominal fat and gene expression related to breast muscle protein metabolism throughout the experimental period. The waxy corn starch diet and a 1.08% dLys level in the diet increased both the percentage of abdominal fat (p < 0.01) and blood total cholesterol (p < 0.05) in the broilers. The waxy corn starch diet significantly upregulated the mRNA expressions of Eif4E, AMPK, FABP1, ACC and CPT1 (p < 0.05). The 1.32% dLys level significantly upregulated the mRNA expressions of mTOR, S6K1, Eif4E, AMPK and PPARα (p < 0.05) and significantly downregulated the mRNA expressions of MuRF and Atrogin-1 (p < 0.05). In summary, the waxy corn starch diet resulted in significantly higher expression levels of fat-synthesis-related genes than lipolysis-related genes, leading to abdominal fat deposition in broilers. Increasing the level of dLys in the diet increased the protein content in muscle by promoting protein synthesis and inhibiting protein degradation and also promoted the expression of lipolysis-related genes, thereby degrading the generation of abdominal fat in broilers. Our findings signify that increasing the dLys level to 1.32% when using the waxy corn starch diet could improve carcass traits.